Agronomic and reclamation strategies to enhance soil fertility, productivity and water accessibility - Rau, Alexey; Zhu, Kai; Nurlan, Balgabayev; Mirobit, Mirdadayev; Yessenkul, Kalybekova; Bek, Meymank Hozhaev; Nabiollina, Madina; Kurmanbek, Zhanymhan; Issakov, Yerlan; Antal, Sándor; Ujj, Apolka; Dávid, Lóránt Dénes (Frontiers in Sustainable Food Systems, 2023)
Over the last decade, yields, profitability of crops on agricultural lands of the Kyzylkum irrigation massif in the south of Kazakhstan, as well as soil fertility are decreasing. After all, the Kyzylkum irrigation basin, located in the Syrdarya River basin, is affected by agronomic, reclamation factors, and human activities such as tourism. Therefore, the purpose of this study is to monitor cotton and alfalfa yields in alfalfa-cotton crop rotations in the Kyzylkum irrigation massif, soil fertility after alfalfa and cotton cultivation under production conditions and profitability of water consumption. The research methodology included experimental and experimental studies to determine productivity, fertility of post-productive soils and profitability of water consumption on nine-pole alfalfa-cotton crop rotation area in the Kyzylkum basin in the Syrdarya river basin (farms Didar, Toishy, Ali-Myrza). As a result of the study, cotton yield in the farm Ali-Myrza increased by 21%, alfalfa yield - by 24%, profit from crop rotation - by 36%, profitability - by 34%, water consumption - by 5-6%. After alfalfa rotation, Ali Myrza farm recorded maximum yield and profit of cotton at 3.5 t / ha and 1316 euros/ha respectively. However, the following year, cotton yields fell to 2.52 t / ha and profits dropped to 576 euro/ha. In the first year, the alfalfa yield was 10 t / ha with a profit of 462 euro/ha; the following year it rose to 14 t / ha with a profit of 967 euro/ha. After two years of growing alfalfa in a six-pole rotation, the root mass in the top 20 cm of soil was 8.89 t/ha. In contrast, rotations with seven (Toishy) and nine (Didar) crops resulted in root masses of 4.68 t/ha and 3.47 t/ha, respectively. The corresponding amount of humus was 1.65%, 1.40% and 1.1%, respectively. Compared to seven-pole and nine-pole rotations of alfalfa and cotton, six-pole rotations increased soil fertility by 30-40%, cotton yield by 18-23%, alfalfa yield by 20-28% and irrigation water consumption by 5-6%. Thus, it was proved that the alfalfa-cotton rotation method is effective in increasing soil fertility, productivity, water productivity and grey soil productivity in Kyzylkum irrigated fields.